NATIONAL DEFENCE STRATEGY AND RESILIENCE OF THE NORTH MACEDONIA SECURITY SECTOR IN THE ERA OF MODERN SECURITY CHALLENGES - Arnaudov, Mitko; Jelisavac Trošić, Sanja; Grujoski, Marjan (The Policy of National Security, 2026)
North Macedonia has become a permanent member of NATO in 2020, in the midst of the global and all-pervading Covid-19 pandemic that did not recognize the boundaries between rich and poor, between large, medium and small countries, between strong and weak health systems. Almost all countries were faced with the catastrophic consequences of this pandemic in the field of human security, but also the sustainability of national economies and health systems. On European level, pandemic was followed by the beginning of the conflict in Ukraine, but it is a challenge that did not directly threaten the security of North Macedonia or other countries on the European continent. This conflict indirectly threatened the economic and specially the energy security of Europe. Pragmatical purpose of the paper is to find an answer to the following question – to what extent the security system of North Macedonia is prepared, as well as adapted to face modern security challenges, such as these? From theoretical perspective, authors will analyse the capacities of small states using the Republic of North Macedonia as a case study in the context of the possibility of adapting and facing modern security challenges.